1979
DOI: 10.1680/macr.1979.31.109.217
|View full text |Cite
|
Sign up to set email alerts
|

Biaxial strees–strain relationships for concrete

Abstract: Synopsis On the basis of experimental results reported more fully elsewhere, a stress-strain relationship is proposed for plain concrete that is applicable to all combinations of biaxial tension and compression. The proposed equation accounts for both non-linear and orthotropic behaviour of concrete. Also based on experimental results, a biaxial ultimate strength criterion is proposed for concrete in the form of a failure stress envelope. The proposed equations are given in a form such that they may be incorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1982
1982
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…In this paper, we mainly study the fracture behavior of the concrete under biaxial compression. According to the previous works [1,2,3,4,5,6,7,8,9], the square plate is usually chosen as the shape of specimens under biaxial loading condition. For example, in the work done by Kupfer, H.B., et al [1], Lee, S., et al [5], and Karavelić, E., et al [9], the size of the specimens are 200 mm × 200 mm × 50 mm, 200 mm × 200 mm × 60 mm, and 150 mm × 150 mm × 30 mm.…”
Section: Numerical Samples and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, we mainly study the fracture behavior of the concrete under biaxial compression. According to the previous works [1,2,3,4,5,6,7,8,9], the square plate is usually chosen as the shape of specimens under biaxial loading condition. For example, in the work done by Kupfer, H.B., et al [1], Lee, S., et al [5], and Karavelić, E., et al [9], the size of the specimens are 200 mm × 200 mm × 50 mm, 200 mm × 200 mm × 60 mm, and 150 mm × 150 mm × 30 mm.…”
Section: Numerical Samples and Resultsmentioning
confidence: 99%
“…In the design of concrete structures, the biaxial strength and fracture behavior are very important. To reveal the mechanism of the concrete biaxial fracture, researchers have carried out a series of experiments [1,2,3,4,5,6,7], including biaxial compression experiments, biaxial tension experiments, and biaxial mixed tension compression experiments. In those studies, the researchers adopted the relative strength to reflect the strengthening effect (or weakening effect) of the complex loading condition.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental research conducted with the aim of investigating the macroscopic fracture conditions for concrete under plane stress states has shown that [2], [3], [6], [8], [11], [12]:…”
Section: Failure Criterion For Concretementioning
confidence: 99%
“…(**) Amount of decrease depends inversely on the absolute value of uniaxial compression: as Co grows, the ultimate strength for k = 1 gets nearer to uniaxial compressive strength (though always remaining greater) [12]. In view of this, the failure locus of concrete under plane stress can be linearized as in Fig.…”
Section: Failure Criterion For Concretementioning
confidence: 99%
See 1 more Smart Citation